2000
DOI: 10.1136/gut.47.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin-1 receptor expression in inflammatory bowel disease: molecular quantitation and localisation

Abstract: Background-Substantial evidence implicates the neuropeptide substance P (SP) in mucosal immunoinflammatory responses. Autoradiographic studies have suggested a disturbance in SP receptor expression in inflammatory bowel disease (IBD). Aims-Because of technical limitations such as poor cellular resolution with autoradiography, we used molecular methods to specifically localise the cellular expression of the neurokinin-1 receptor (NK-1R) in IBD colon, and to quantitate NK-1R mRNA expression levels therein. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
119
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(133 citation statements)
references
References 45 publications
13
119
1
Order By: Relevance
“…Also revealed was the importance of IL-12 and IL-10 for the control of mucosal T cell NK-1R expression. This may be physiologically important, since NK-1R is heavily expressed on mucosal T cells in human IBD (10). The piroxicam-IL-10 model of IBD will allow further exploration into the roles of tachykinins and their receptors in the control of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also revealed was the importance of IL-12 and IL-10 for the control of mucosal T cell NK-1R expression. This may be physiologically important, since NK-1R is heavily expressed on mucosal T cells in human IBD (10). The piroxicam-IL-10 model of IBD will allow further exploration into the roles of tachykinins and their receptors in the control of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In human IBD there is increased NK-1R mRNA expression (9) in the tissue. Goode et al (10) showed, using quantitative PCR, a 7-fold increase in NK-1R transcripts in CD colon and a somewhat more modest increase in ulcerative colitis. Compared with normal control colon, however, immunohistochemistry revealed no ectopic sites of NK-1R expression.…”
mentioning
confidence: 99%
“…For this reason, NK1 receptor antago-nists are used as antidepressants (Fuchs et al 2005). Several reports have demonstrated the presence of NK1R in different neuronal and non-neuronal cells in the gastrointestinal tract (Sternini et al 1995;Goode et al 2000). In pathological states, such as inflammation in Crohn's disease, NK1R expression is up-regulated (Renzi et al 2000).…”
Section: Oryctolagus Cuniculus Nk2r Sus Scrofa Nk2rmentioning
confidence: 99%
“…The NK-1R has been identified in epithelial cells in rodent models of colonic inflammation (9,10) and in patients with UC as well as Crohn disease (11)(12)(13)(14). However, not all of these studies are in agreement regarding epithelial NK-1R expression in UC: some studies have shown an increase (12,13), whereas others have not (11,14). The NK-1R has been identified in many cancers, including skin, gastrointestinal, laryngeal, pancreatic, ovarian, brain, thyroid, and breast cancers (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…SP's primary receptor, the neurokinin-1 receptor (NK-1R), can mediate a variety of physiologic and pathophysiologic responses, including cell proliferation, migration, and inflammation (8). The NK-1R has been identified in epithelial cells in rodent models of colonic inflammation (9,10) and in patients with UC as well as Crohn disease (11)(12)(13)(14). However, not all of these studies are in agreement regarding epithelial NK-1R expression in UC: some studies have shown an increase (12,13), whereas others have not (11,14).…”
mentioning
confidence: 99%